Intestinal blood flow alterations in postoperative intraabdominal adhesion formation and the role of endothelin-1 blockade [Ameliyat sonrasi karin içi yapişiklik oluşumunda baǧirsak kan akimindaki deǧişiklikler ve endotelin-1 bloǧunun rolü] - (:unkn) unknown (My University, 2006)
BACKGROUND: The current study was planned to investigate intestinal blood flow alterations and the role of ET-1 receptor blockade in the formation of postoperative intraperitoneal adhesion formation. METHODS: Twenty-eight adult Wistar Albino rats weighing between 250 g and 300 g were divided into four groups. Control group (group 1; n=7) did not undergo any operation. Sham group (group 2; n=7) had only laparotomy. In the adhesion group (group 3; n=7), peritoneal patch (1x1 cm) excision from the right abdominal wall and cecal abrasion were done as "adhesion model operation". One week following this, treatment group (group 4; n=7) received a non-selective ET-1 receptor blocking agent bosentan (30 mg/kg, IP) intra-abdominally, once a day for four days. Intestinal blood flow through the superior mesenteric artery was measured, on postoperative seventh day. Adhesion severity and extension as well as myeloperoxidase activity in the adhesion were calculated. RESULTS: Mean intestinal blood flow significantly increased in adhesion group (81.9±5.6 ml/100 g) when compared to group 1 (65.5±1.2 ml/100 g). Bosentan caused a significant decrease (44.3±6.9 ml/100 g) in intestinal blood flow when compared to group 1 and group 2. Sham group (62.2±1 ml/100 g) had similar blood flow level with the control group (65.5±1.2 ml/100g). Adhesion scores were similar in adhesion and Bosentan groups. Sham group had almost no adhesions. Myeloperoxidase activity in adhesion tissue was significantly higher in bosentan group. CONCLUSION: Non-selective ET-1 receptor blockade has no effect on prevention of the formation of intra-abdominal adhesion, but causes a decrease in intestinal blood flow. Adhesion formation increases intestinal blood flow. Adhesion formation is accompanied by increased polymorphonuclear infiltration despite bosentan treatment.
Keywords: Adhesions; Bosentan; Endothelins; Rats, Wistar; Receptors, Endothelin/ antagonists & inhibitors